2020
DOI: 10.3389/fcell.2020.547342
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 Promotes the Osteogenic Differentiation of Tendon-Derived Stem Cells and the Pathogenesis of Heterotopic Ossification in Rat Tendons via the mTOR Pathway

Abstract: Heterotopic ossification (HO) is a pathological condition involved in tendinopathy. Adipokines are known to play a key role in HO of tendinopathy. Nesfatin-1, an 82-amino acid adipokine is closely reportedly associated with diabetes mellitus (DM), which, in turn, is closely related to tendinopathy. In the present study, we aimed to investigate the effects of nesfatin-1 on the osteogenic differentiation of tendon-derived stem cells (TDSCs) and the pathogenesis of tendinopathy in rats. In vitro, TDSCs were incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…In addition, these mRNAs were involved in 51 signalling pathways, such as PI3K‐Akt signalling pathway, metabolic pathways, glycolysis/gluconeogenesis pathways and mTOR signalling pathway (Table ). Among these pathways, PI3K‐Akt signalling pathway, mTOR signalling pathway and so on have been reported to be positive regulators of osteogenic differentiation in MSCs, 30,31 so we speculated that the stronger osteo‐differentiation ability of hPDLSCs could be regulated by these signalling pathways. The top 10 GO terms (BP, CC, MF) and pathway terms are shown in Figure 4B and Figure 4E according to enrichment score.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, these mRNAs were involved in 51 signalling pathways, such as PI3K‐Akt signalling pathway, metabolic pathways, glycolysis/gluconeogenesis pathways and mTOR signalling pathway (Table ). Among these pathways, PI3K‐Akt signalling pathway, mTOR signalling pathway and so on have been reported to be positive regulators of osteogenic differentiation in MSCs, 30,31 so we speculated that the stronger osteo‐differentiation ability of hPDLSCs could be regulated by these signalling pathways. The top 10 GO terms (BP, CC, MF) and pathway terms are shown in Figure 4B and Figure 4E according to enrichment score.…”
Section: Resultsmentioning
confidence: 96%
“…Pathway analyses showed that these mRNAs were significantly enriched in 57 signalling pathways including aminoacyl‐tRNA biosynthesis pathway, metabolic pathways, biosynthesis of amino acid pathway, MAPK signalling pathway and so on (Figure 4D, Table ). Notably, MAPK signalling pathway has been reported to be a classical pathway that regulates the osteogenic differentiation of MSCs, 30,31 so we speculated that this pathway could play important roles in hPDLSCs and hGMSCs during osteogenic differentiation. The top 10 pathways are shown in Figure 4D according to enrichment score.…”
Section: Resultsmentioning
confidence: 98%
“…To determine the protective role of SP in vivo, an Achilles tenotomy rat model was used to mimic the in vitro tendinopathy model [ 6 , 7 , 32 ]. The flowchart for the animal procedures is shown in Figure 7(a) .…”
Section: Resultsmentioning
confidence: 99%
“…Since aging is a potential detrimental factor for tendon homeostasis, the effect of senescence on tendinopathy in TDSCs was investigated [ 44 , 45 ]. Our previous study reported that senescence in TDSCs is a characteristic of HO and chronic inflammation [ 6 , 7 ]. Similar to previous studies, more senescent TDSCs were detected under tendinopathic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation